The ideologies and identities of insanity the emergence of lunatic asylums in colonial Kerala - Shareena Jasmin. P. K (MES Kallady College, Mannarkkad, Palakkad, University of Calicut, 2025)
The thesis entitled “The Ideologies and Identities of Insanity: The Emergenceof Lunatic Asylums in Colonial Kerala” examines the establishment of Westernpsychiatry and its offshoot lunatic asylums in colonial Kerala. This work attempts toanalyze the colonial narratives underlying the introduction of Western psychiatry andto deconstruct the notion of the hegemony of Western medicine by examining theenduring popularity of Indigenous healing techniques in the region under study,which, in fact, offer a rich tapestry of healing approaches, accepting, accommodating,and acknowledging diverse forms of care. The research is a pioneering contributionto the history of colonial psychiatry in the regional context of Kerala, as no previousstudy has comprehensively addressed the establishment of the three major lunaticasylums of colonial Kerala. The methodology of the study largely relies on analyticaland descriptive techniques, and the sources for the study comprise various primaryand secondary materials. Primary documents, such as archival data, oral testimonies,newspaper reports, etc., were extensively used, alongside secondary sources likebooks, articles, and other scholarly literature, to reconstruct the notion of madness incolonial Kerala society.The research problem revolves around the question of the hegemony of Westernpsychiatry over the native systems of healing. In order to explore this, the researcherhas examined its different dimensions, investigating the region's multiple therapeuticregimes alongside the different facets of Western psychiatry and its healing practices.Based on this, the study has put forward multiple objectives, including the analysis ofthe region’s collective understanding of madness, socio–political and psychologicaldimensions behind the introduction of Western psychiatry, the gendered concepts ofmadness, the indigenization of psychiatric practices, the wide varieties of native systemsof healing, etc.Based on the research findings, the study puts forward the argument that thehegemony of colonial psychiatry was deliberately constructed and carried out the ideaby the colonizers to counterpart the existence and effectiveness of native traditionsand to justify colonial superiority through the perceived supremacy of Westernpsychiatry. The tremendous popularity of Indigenous practices and their simultaneousexistence with institutional psychiatry proves that the colonial attempt to jeopardizenative tradition was partial and cannot argue for an overarching hegemony of Westernmedicine over native forms of healing. Particularly in the Kerala scenario, the deepxiroots of Ayurveda practices and the ongoing practices of spiritual healing in differentcommunities show that the hegemony of colonial medicine was theoretically strongin the colonial quarters but was pragmatically feeble among the natives since they hadmultiple therapeutic choices to express their idioms of illness both mental andphysical.The discourse on the relationship between medical power and colonial poweralways draws the conclusion of a hegemonic regime. However, it is important toremember that medical practices were not always hegemonic simply because theywere applied within a colonial context. The medicalization of colonial power does notalways correspond with the colonization of the native body and mind. The interactivepractices and processes between Western medicine and indigenous traditions, andabove all, the popularity of native traditions among natives, go against the establishedviewpoint of colonial hegemony. Though colonialism used lunatic asylums as a toolof the empire to legitimize colonial rule, to some extent, it also embodied the notionsof kindness, humanity, and moral management. These all suggest the dynamicdimensions of colonial psychiatry beyond hegemony.However, in the course of time, Kerala was subjected to the “new” definitionof madness, and this “new” knowledge originated and developed in a different culturalcondition of the Western world. This may seem paradoxical from a peripheral reading,but an in-depth understanding suggests that the acceptance of modern Psychology inKerala was a process of negotiation and accommodation, rather than a hegemonicconfrontation and conflict between Western and traditional healing practices. Thedynamic medical geography of Kerala, deeply rooted in the accommodation andadaptation of varying forms of therapeutics, accepted the institutions of mentalhospitals and, at the same time, continued its traditional healing practices with muchpopularity during the colonial period. Psychiatry could not drown the indigenousnotions of healing that pulsate in the life and mind of the masses. The attempts tointeract with and indigenize Psychiatry by the native methods of healing by wideningtheir boundaries to the “new” concepts and practices of healing show the flexibilityand adaptability of native systems of healing. It is possible that colonial Keraladeveloped an enfolding worldview tolerating modern Psychology along with otherpluralistic treatment methods of insanity.
Keywords: Lunatic Asylums; Western Psychiatry; Mental Illness; Indigenous Healing; Hegemony; Gendered Madness.